Experimental researches of the persistent bearing at face fluctuations of a crest and axial fluctuations of a shaft in relation to the case - Хлопенко, Н.Я.; Сидорика, И.Н. (Problems of Tribology, 2014)
Conducted in a course of experiment of research, calculations and measurements of a thickness of an oil film under a pillow point of support at face fluctuations a crest, a warp of the case and the compelled fluctuations of a shaft in relation to the case have shown good coincidence between the theory and experience.